Morpho-physiological and yield traits of sesame (Sesame indicum L.) varieties under rainfed conditions: TRAITS OF SESAME VARIETIES UNDER RAINFED CONDITIONS - P RATNAKUMAR; K N RAVITEJ; B B PANDEY; S NARENDER REDDY; V GOURI SHANKAR; D PADMAJA (Journal of Oilseeds Research, 2019)
A field experiment was conducted during kharif, 2018 to evaluate the performance of 10 sesame varieties viz., RT-346, RT-351, RT-127, GT-10, TKG-22, SWETHA, JCSDT-26, DS-1, YLM-66 and KMS-4-322 for morphological, physiological and yield traits under rainfed conditions in randomized block design with three replications. Results indicated that the varieties significantly differed for morphological parameters viz, plant height (PH), number of branches (NB), leaf area (LA), days to 50% flowering, days to maturity, and for physiological parameters viz., SPAD chlorophyll meter reading (SCMR), leaftemperature (LT), relative water content (RWC) and for yield parameters viz., number of capsules per plant, single capsule dry weight, number of unfilled capsules per plant, 1000 seed weight, seed yield, total dry matter and harvest index (HI).Variety JCSDT-26 recorded high seed yield, number of capsules per plant, single capsule dry weight along with maximum SCMR, RWC, minimum LT indicating the role of these physiological traits for better performance of this variety under rainfed conditions; followed by Swetha, RT-127, GT-10 and YLM-66. Based on the performance of the variety JCSDT-26, it could be concluded that the variety could be suitable for cultivation under rainfed conditions.